ASSESSMENT OF REPRODUCTIVE POTENTIAL IN MEN WITH NON-OBSTRUCTIVE AZOOSPERMIA AND CONCOMITANT GENETIC ABNORMALITIES UNDERGOING MICRO-TESE AT HOSPITAL OF POST AND TELECOMMUNICATIONS (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the prevalence and characteristics of genetic abnormalities in men with non-obstructive azoospermia (NOA), and to analyze sperm retrieval and reproductive outcomes following microdissection testicular sperm extraction (micro-TESE) at Hospital of Post and Telecommunications.Methods: This retrospective descriptive study included 309 patients diagnosed with NOA who underwent micro-TESE at the Center for Assisted Reproduction, Bưu Điện Hospital, between September 2022 and September 2024. Among them, 90 patients with confirmed genetic abnormalities and complete medical records were enrolled for analysis. Evaluated parameters included clinical characteristics, genetic testing results, sperm retrieval rates following micro-TESE, and reproductive outcomes after intracytoplasmic sperm injection (ICSI).Results: The prevalence of genetic abnormalities among patients with NOA was 29.1%. Sex chromosome abnormalities accounted for 96.7% of cases. Klinefelter syndrome was the most common abnormality (70%), followed by Y chromosome AZFc microdeletions (22.3%). The overall sperm retrieval rate using micro-TESE was 54.4%. The sperm retrieval rate in patients with Klinefelter syndrome and AZFc microdeletions were 54% and 55%, respectively. Among cases with successful sperm retrieval, the cumulative live birth rate following ICSI was 61.2%.Conclusions: Genetic abnormalities are highly prevalent among men with NOA, predominantly involving sex chromosome abnormalities. Micro-TESE demonstrated favorable efficacy in sperm retrieval and assisted reproductive outcomes in this patient population, particularly in individuals with Klinefelter syndrome and AZFc microdeletions. The combination of micro-TESE and ICSI plays an important role in the management of male infertility associated with genetic abnormalities.
Keywords: Non-obstructive azoospermia, micro-TESE, Klinefelter syndrome, Y chromosome microdeletion, male infertility.